MODERN APPROACHES IN DIAGNOSIS AND TREATMENT OF PROSTATE CANCER (LITERATURE REVIEW) (ResearchJet Journal of Analysis and Inventions, 2021)
Prostate cancer has one of the leading positions among the incidence of cancer and still has a higher position on the aggressiveness of the process. This research briefly analyzes the current condition of the issue of prostate cancer, assesses the modern aspects of early diagnosis, prognosis and complex treatment.